Pengaruh Pendapatan Asli Daerah Dan Belanja Modal Pada Peningkatan Indeks Pembangunan Manusia Provinsi DKI Jakarta Tahun 2015 – 2022 - Harun Al Rasyid; Agus Tri Indah K (Owner : Riset dan Jurnal Akuntansi, 2023)
The implementation of regional autonomy and fiscal decentralization gives regional governments the authority to increase regional revenues and realize distributive benefits so that they can determine regional development priorities. This human development concept prioritizes four elements, including productivity, equity, sustainability and empowerment. The aim of this research is to understand how capital expenditure and PAD influence increasing the human development index. DKI Jakarta Province was the location for this research. The 2015-2022 APBD Performance Report and 2015-2022 HDI statistics are secondary data sources used in this research. By using multiple regression analysis, the requirements for traditional hypothesis testing and model feasibility testing are met. Regional initial income does not have a positive impact on the human development index. Capital expenditure does not have a negative impact on the human development index. For simultaneous calculations (F statistical testing), the conclusion is that regional sources of income and capital expenditure simultaneously influence the human development index. Based on hypothesis testing, it shows that PAD and capital expenditure have a positive and significant effect on increasing the human development index. This positive and significant influence means that the more PAD and capital expenditure increase, the higher the HDI will be. This increase was due to the allocation of initial regional income and investment expenditure being used well so that planned activities could be carried out smoothly.